“The Story of Magielona, Princess of Naples”: The Question of the Basis of the Polish Translation - Wierzbicka-Trwoga, Krystyna; Winiarska-Górska, Izabela (Porównania, 2023)
The paper seeks to establish the basis of the Polish translation of the Old French romance about the “beautiful Magielona.” The Polish version was translated in the sixteeth century, though not from the French, but via a German or Czech version. Until now, there were no studies on the base text of the Polish translation, transmitted in several seventeenth-century editions. The analysis presented in our paper concerns the delimitation of the text, i.e. the division of content into chapters in the Polish prints in comparison to the German editions of the sixteenth century and to the Czech version (transmitted from the eighteenth century), as well as the comparison of the opening sentences of the chapters. It allows for the conclusion that the Polish translation arose most probably from the German version, from an edition containing the primary segmentation of the German text, which in the second half of the sixteenth century was published in a secondary edition with a finer segmentation of the text.